Azepines, Chemistry, Synthesis and Reactions - Khalid M. Darwish; Nafisa I. Al-Tarbali (International Journal of Minerals, 2025)
Azepines, which consist of a seven-membered cyclic compound featuring six carbon atoms, an additional nitrogen atom, and no double bonds between carbons, form a diverse group within organic chemistry. The fully hydrated form of this compound is called azepam (C6H13N). Compounds and their variants play crucial roles in pharmaceutical research due to their biologic attributes like cancer-fighting, bacteria-killing, fungus-busting, virus-suppressing, and inflammation-reducing capabilities. Various organic molecules found within nature draw attention from scientists across multiple fields due to potential therapeutic applications they offer, such as creating effective medications for various health conditions. Indeed, synthesizing azepines can differ based on the specific condition; however, certain techniques utilize hazardous volatile substances like hydrogen azide for expanding rings into larger ones through conversion processes. Recent research has hinted at utilizing heavier transition metal catalysts including gold, platinum, rhodium, silver, nickel, molybdenum, among others, in an asymmetric approach towards creating these compounds via organic catalysis. Different reactions entail the stepwise formation of azepines through photoinitiated processes. Additionally, this critique delves into elucidating the Specific Antidepressant Response (SAR) associated with azepam compounds. We shall scrutinize numerous methodologies within this assessment and identify notable physiological impacts resulting from those processes.
Keywords: Azepine compounds; asymmetrical synthetic methods; ring enlargement techniques; significance in biology; toxicity of heavy metals